RESEARCH ON TRAFFIC CONGESTION DETECTION FROM CAMERA IMAGES IN A LOCATION OF DA LAT - Nguyen Thi Luong (Tạp chí Khoa học Đại học Đà Lạt)
Many researchers are interested in traffic congestion detection and prediction. Traffic congestion occurs increasingly in many cities in Vietnam, including the city of Da Lat. This paper focuses on SVM, CNN, DenseNet, VGG, and ResNet models to detect traffic congestion from camera images collected at Nga 5 Dai Hoc, Da Lat. These images are labeled with the words traffic congestion or no traffic congestion. The experimental results have an accuracy of over 93%. The study is an initial contribution to a future system for predicting traffic congestion in Da Lat when the camera system is fully installed.